Leaving Las Vegas [videorecording (DVD)] - Figgis, Mike; Figgis, Mike; Cage, Nicolas, 1965-; Shue, Elisabeth; Sands, Julian; O'Brien, John, 1960-1994 (Sandpiper Pictures, 2025)
When a drunk leaves behind his life and goes to Las Vegas to drink himself to death, he meets a prostitute who tries to save him.